2017
DOI: 10.1016/j.rmcr.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy “Shock” a case series of PD-L1 100% and pembrolizumab first-line treatment

Abstract: In this decade a “bloom” of novel therapies has been observed for non-small cell lung cancer. We have new tools for the diagnosis of lung cancer and also we can re-biospy easier than before in different lesions and obtain tissue samples in order to investigate whether a patient can receive new targeted therapies. Immunotherapy has been well established previously for other forms of cancer, and nowadays it is also available for lung cancer. There are two immunotherapies for now nivolumab and pembrolizumab which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Accordingly, the cavity formation and hemoptysis could not have been associated with corticosteroid therapy, nor were they consistent with aspergillus infection. The case in our study is inconsistent with that reported by Zarogoulidis 13 et al in which a lung mass turned into an abscess together with the patient suffering from fever, infection indicated by laboratory findings and effective antibiotic treatment. Reviewing the studies of hemoptysis related to tumor treatment together with the findings in our case, we believe that the severe bleeding event was caused by the giant central location of the tumor that was significantly PD-L1 positive, shrinkage of the mass and large area necrosis with cavity formation after immunotherapy, as well as possible vascular involvement.…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, the cavity formation and hemoptysis could not have been associated with corticosteroid therapy, nor were they consistent with aspergillus infection. The case in our study is inconsistent with that reported by Zarogoulidis 13 et al in which a lung mass turned into an abscess together with the patient suffering from fever, infection indicated by laboratory findings and effective antibiotic treatment. Reviewing the studies of hemoptysis related to tumor treatment together with the findings in our case, we believe that the severe bleeding event was caused by the giant central location of the tumor that was significantly PD-L1 positive, shrinkage of the mass and large area necrosis with cavity formation after immunotherapy, as well as possible vascular involvement.…”
Section: Discussioncontrasting
confidence: 99%
“…However; for immunotherapy to be a successful therapy the immunological status plays a crucial role. Several factors are responsible for the adverse effects of immunotherapy, these could be summarised to the virus or vaccines that a patient had be exposed and to whether or not there is an underlying or undiagnosed systematic disease [19] , [20] . To our knowledge the patient that we presented did have a systematic underlying disease and the development of vitiligo was due to the nivolumab administration.…”
Section: Discussionmentioning
confidence: 99%
“…Upon diagnosis we have to acquire the best sample possible which means acquiring TH as best possible. It has been observed in paraffin blocks with the same technique, e.g., DAKO, Biocare, that different slices might contain different PD-L1 expression (11). There is the possibility that patients that were included in immunotherapy studies had higher PD-L1 expression that initially diagnosed, a retrospective analysis of the specimens could assist in clarifying this issue.…”
mentioning
confidence: 99%